Análise do comportamento de plantas industriais mediante a inserção de ciberataques ao protocolo de rede Modbus TCP - Alvarez, Rafael Abrão (Universidade Federal de São Carlos, 2026)
The use of Programmable Logic Controllers (PLCs) and industrial communication networks is essential in automated processes to ensure efficiency and monitoring. However, large-scale integration of Real Time Ethernet based networks introduces vulnerabilities, such as susceptibility to interference and cyberattacks. This work proposes to analyze the behavior of a simulated industrial network under cyberattack conditions. The chosen communication protocol is Modbus TCP, a widely used protocol in industrial environments, which connects an industrial plant modeled in Factory I/O to a PLC programmed in ladder using CODESYS. Using Wireshark to capture network traffic and Python’s Scapy library to inject attacks, the objective is to identify operational impacts and weaknesses inherent in the protocol. The simulation revealed critical failures, such as unauthorized changes to data and compromised communication, as well as the malfunctioning of the industrial plant, highlighting the lack of security and the absence of mechanisms to verify the authenticity of packets in the Modbus TCP protocol. The results aim to reinforce the need for robust security measures in industrial networks and to encourage migration to updated protocols aligned with contemporary cybersecurity demands.
Behavior analysis of industrial plants subjected to cyberattacks on the Modbus TCP network
Keywords: Automação Industrial; Ciberataques; Modbus TCP; ENGENHARIAS::ENGENHARIA ELETRICA::ELETRONICA INDUSTRIAL, SISTEMAS E CONTROLES ELETRONICOS::AUTOMACAO ELETRONICA DE PROCESSOS ELETRICOS E INDUSTRIAIS; 9. Indústria, Inovação e Infraestrutura